Association between brain corpora amylacea and Alzheimer's disease - Kurata, Hiromitu; Nushida, Hideyuki; Yoshida, Nanaka; Tokunaga, Itsuo; Yoshino, Takumi; Nishimura, Akiyoshi; Umemoto, Hitomi; Ito, Asuka; Iseki, Hirofumi (SHIKOKU ACTA MEDICA, 2025)
In this study, we investigated the origin of the brain corpora amylacea （CA） and its association with Alzheimerʼs disease, with the aim of identifying indicators for dementia assessment. The cases were autopsied at the Department of Forensic Medicine, University of Tokushima, and the postmortem examinations were performed within 48 h of death.　The immunostaining results showed that almost all brain CAs were positive for ubiquitin and neurofilaments, which suggests that brain CAs contain components derived from protein processing systems and that the proteins are of neuronal origin.　We analyzed the correlation between the number of brain CAs and the sum of neurofibrillary tangles and senile plaques, and identified a significant positive correlation only in male cases.　　Therefore, we suggested that the number of brain CAs in the hematoxylin and eosin-stained brains of male patients with a strong positive correlation can be evaluated as a simple preliminary test for the Braak classification using Gallyas–Braak staining.